Bald on Record Strategy and Politeness in Cyber Political Communication: A Pragmatic Analysis of Speech in the 2024 Indonesian Presidential Election - Yanti, Yusrita; Thamrin, Temmy; Hasan, Diana Chitra; Izmayanti, Dewi Kania; Irma, Irma; Pramujiono, Agung (Universitas Muhammadiyah Malang, 2026)
This study examines the dominance of the bald-on-record (BOR) strategy and forms of politeness in cyberpolitical communication during the 2024 Indonesian Presidential Election. The phenomenon of direct speech without mitigation is a significant issue due to its association with increasing discursive tension and public polarization in the digital space. The purpose of this study is to analyze the distribution, pragmatic functions, and sociotechnical factors influencing the emergence of BOR, as well as positive and negative politeness, in online political discourse. The study uses a qualitative descriptive approach based on an interpretive paradigm. Data were obtained from YouTube video transcripts depicting speeches, debates, and political discussions from July 2023 to March 2024. These were then analysed using Brown and Levinson's (1987) politeness model and Culpeper's (2016) impoliteness theory. The results show that BOR dominates 70% of total speech, while positive and negative politeness account for 20% and 10%, respectively. BOR emerges in the form of vulgar insults, ideological stigma, and re-contextual irony due to the collapse of the digital context. The main triggering factors include the effects of online disinhibition, engagement algorithms, and the formation of digital community enclaves that normalize blunt communication styles. The study's conclusions confirm that BOR is not simply linguistic impoliteness, but rather a rhetorical strategy that utilizes platform logic to signal identity, mobilize emotions, and achieve political visibility. This research contributes to the development of politeness theory and provides practical recommendations for digital pragmatic literacy in Indonesian political communication.